80.4k views
4 votes
What’s the inverse of the function F(x)=2x+1

2 Answers

1 vote

Answer:

f-1(x) = (x - 1)/2.

Explanation:

Let f(x) = y

y = 2x + 1

2x = y - 1

x = (y - 1)/2

Now replace x by the inverse of f(x) ( that is f-1(x) ) and y by x:

f-1(x) = (x - 1)/2.

User Joelhoro
by
6.0k points
3 votes

Answer:

Explanation:

1. Replace F(x) with y.

2. Interchange x and y in y = 2x + 1: x = 2y + 1

3. Solve this result for y: 2y = x - 1, or y = (x - 1)/2

4. Replace y with:

-1

F (x):

-1 x - 1

F (x) = -----------

2

User Jazline
by
6.1k points